Rumah Tok Menteri II: a continuation of generations - Sapian, Abdul Razak; Abdul Majid, Noor Hanita; Abdul Rahim, Zaiton; Denan, Zuraini (IIUM Press, 2013)
This book explains about the historical background of a house originally occupied by the Minister for Sultan of Kedah. Situated in Alor Setar, Kedah. The book established a clear and precise explanation on the development of Malaysia's early settlements up to Colonial period. It particularly focus on an overview of the colonial bungalow named Rumah Tok Menteri 2. This house was built by En Ismail Hakim Teh, a minister of Kedah during the era of Sultan Abdul Hamid Halim Shah. Its architectural style, influences and building systems should provide readers with ample information on the culture of the Malay people in the 1880's. The book emphasizes on the architectural significance of the building from the history of occupancy to the architectural detail of construction and material.